Break every rule - Freeman, Brian, 1963- (Blackstone Publishing, 2024)
"Tommy Miller is a man with deadly skills, hiding in Florida under a false identity. After being set up on an overseas mission, he's on the run from terrorists--and from the government who betrayed him. So when his wife and daughter are violently abducted, it seems his ghosts are finally catching up with him. But Tommy isn't the only one with secrets. His wife, Teresa, has been concealing her own dangerous past, and as Tommy races to rescue his family, he must peel away the clues she's left behind. With a hotshot police detective, Lindy Jax, close on his trail, Tommy follows a twisted path from Florida to the Bahamas, one that brings him face-to-face with ruthless enemies. His search for answers soon puts him on the wrong side of the law--hunted by the police and pursued by men who want him dead. Worst of all, if he hopes to save Teresa and their daughter, Rosalita, he must become the man he once was--a killer operating from the deepest shadows. But when the lives of the people you love are at stake, rules are made to be broken"--